Analisis Miskomunikasi Dalam Proses Pembelajaran Di Lingkungan Sekolah: Studi Kasus SMP Negeri 5 Curug Kabupaten Tangerang Tahun 2024 - Miftahul Falah; Isniyunisyafna Diah Delima; Mad Yoman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze miscommunication in the learning process at SMP Negeri 5 Curug, Tangerang Regency in 2024. Miscommunication is one of the factors that can have an impact on the effectiveness of the learning process and the achievement of student learning outcomes. This research uses a qualitative approach with a case study method. Data was collected through observation, in-depth interviews and documentation of teachers, students and other related parties at SMP Negeri 5 Curug. Data analysis was carried out using descriptive qualitative analysis techniques to identify forms of miscommunication, causal factors, and their impact on the learning process. The research results show that miscommunication occurs in various forms, such as misunderstanding of instructions, different interpretations of material, hybrid online learning systems, small class sizes and lack of two-way communication between teachers and students. Factors causing miscommunication include lack of literacy among students, network factors, and limited facilities and infrastructure. The impact of this miscommunication is decreased student motivation to learn, low participation in class, and achievement of learning outcomes that are not optimal.